Aland island eye disease: clinical and electrophysiological studies of a Welsh family. Issue 5 (May 1995) - Hawksworth, N R; Headland, S; Good, P; Thomas, N S; Clarke, A
Abstract : Clinical and molecular genetic studies were performed on a single, large, white family, in which congenital nystagmus and moderate to high refractive error segregated as a sex linked trait with manifestation in some female carriers. In this family, affected males demonstrate myopia, but a high proportion of female carriers, and some of the possibly affected males, show hypermetropia. Clinical ophthalmic examination and electrodiagnostic studies of retinal function were fully compatible with a diagnosis of either incomplete congenital stationary night blindness or of Aland island eye disease. Previous studies have mapped both disorders to the proximal short arm of the X chromosome: our molecular studies support this localisation. Incomplete congenital stationary nightblindness and Aland Island eye disease could be considered as a single entity.